Air-Stable Electron Depletion of Bi2Se3 Using Molybdenum Trioxide into the Topological Regime - Edmonds, M.; Hellerstedt, J.; Tadich, A.; Schenk, A.; O'Donnell, Kane; Tosado, J.; Butch, N.; Syers, P.; Paglione, J.; Fuhrer, M. (American Chemical Society, 2014)
We perform high-resolution photoelectron spectroscopy on in situ cleaved topological insulator Bi2Se3 single crystals and in situ transport measurements on Bi2Se3 films grown by molecular beam epitaxy. We demonstrate efficient electron depletion of Bi2Se3 via vacuum deposition of molecular MoO3, lowering the surface Fermi energy to within ~100 meV of the Dirac point, well into the topological regime. A 100 nm MoO3 film provides an air-stable doping and passivation layer.